Safety profile of the meningococcal conjugate vaccine (Menafrivac™) in clinical trials and vaccination campaigns: a review of published studies - Jerome Ateudjieu; Beat Stoll; Anne Cecile Bisseck; Ayok M. Tembei; Blaise Genton (Human Vaccines & Immunotherapeutics, 2020)
The study aimed to assess the capacity of AEFI surveillance during vaccination campaigns with the new conjugate meningitis vaccine (MenAfrivac). A systematic review of studies on MenAfrivac™ published in English during 2001–2016 was done.AEFIs incidence (I) was estimated and compared between MenAfrivac™ clinical trials and immunization campaigns using incidence difference (Id). Nine studies were included with an overall local AEFI I of 11,496/100,000 doses administered per week in clinical trials and 0.72/100,000 doses in immunization campaigns. An Id of 11,497.92 [11,497.91-11,497.93] and 17,243.20 [17,241.80-17,245.90] per 100,000 doses administered per week for overall local and systemic AEFI, respectively, were observed with highest from clinical trials. The incidence of AEFIs after MenAfrivac™ vaccination was far lower in campaigns than in clinical trial studies. Current capacity of AEFI surveillance during vaccination campaigns requires extensive re-assessment of its structure and capacity.